Rhizospheric cymbopogon citratus-staphylococcus succinus interactions for phytoremediation of dibenzofuran contaminated soil - Nordin, Noor Faizul Hadry; Mat Shaari, Nurul Elyni; Zainuddin, Zarina; Md Tajudin, Md Tajol Faeiz (Malaysian Society for Molecular Biology and Biotechnology, 2017)
Chloroaromatic compounds such as dioxins and dioxin-like compounds is categorized as a highly persistent chemical and accumulates in the environment as well as increasing their distribution in our ecosystem. Phytoremediation is one of the tolerable ways that has been operated to battle out the problem of contaminants. is study investigated the lemongrass (Cymbopogon citratus) traits and soil enzyme activities upon dibenzofuran (DBF) pollution and inoculation of Staphylococcus succinus in soil. Lemongrass was planted into uncontaminated soil and DBF-contaminated soil. Four treatments were conducted; soil, soil with plant, soil with bacteria, and soil with plant and bacteria. After 30 days exposure, the plant traits such as plant length, biomass, chlorophyll content and soil enzymes activities were examined to investigate the sensitivity of lemongrass towards DBF. e presence of DBF in soil, plant length and aboveground and belowground mass were decreased compared to control. However, with inoculation of Staphylococcus succinus in soil, these plant traits were signi cantly higher than control, suppressing the e ects of DBF. e chlorophyll content of lemongrass indicated slightly di erence showing a less or no e ect of DBF. Nevertheless, enzyme activities of asparaginase and protease exhibited higher activity than uncontaminated soil. DBF reduction can be seen by GC-MS analysis where symbiosis of lemongrass and bacteria showed the highest reduction percentage.